Improving Students’ Learning Outcomes in Learning English by Using Interactive Multimedia - Putri , Anisa Hersa; Frimasary, Amelia Eka; Yunita, Wisma (TRIADIK, 2023)
Abstract Technology can change the paradigm of teacher-centered to be student-centered. One of the advantages of the technology is in utilizing multimedia. Multimedia is one type of media that can be used as the solution to improve the student motivation and participation in learning process. This classroom action research aims to improve English learning outcomes of students in SMA Negeri 2 Kota Bengkulu by using interactive multimedia. The research sample is students of class X IPS A consisting of 36 students. Samples were taken by purposive. The stages of the research consisted of Planning, Implementation, Observation and Reflection. The result showed that before being treated, there was 41.6 % students who had grades above the minimum criteria. Then, students’ learning outcomes increased to 58.3 % in the first cycle, and 83.3 % in the second cycle. It can be concluded that interactive multimedia can improve learning outcome of the students.